2016
DOI: 10.2147/ott.s108242
|View full text |Cite
|
Sign up to set email alerts
|

Clinical efficacy of first-generation EGFR-TKIs in patients with advanced non-small-cell lung cancer harboring <em>EGFR</em> exon 20 mutations

Abstract: PurposeSubsets of non-small-cell lung cancer patients with epidermal growth factor receptor (EGFR) mutations carry uncommon subtypes. We evaluated the efficacy of first-generation EGFR-tyrosine kinase inhibitors (TKIs; erlotinib, gefitinib, and icotinib) in patients with non-small-cell lung cancer carrying insertions and T790M and S768I mutations in EGFR exon 20.Patients and methodsPatients carrying EGFR exon 20 insertion/T790M/S768I mutations and treated with EGFR-TKIs were evaluated from 2005 to 2014 in Zhej… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(61 citation statements)
references
References 27 publications
4
54
1
2
Order By: Relevance
“…The G719X, S768I and L861Q carriers contributed most primary resistance patients in our study. Robust evidence has shown the poor response to the first‐generation TKI in G719X/S768I/L861Q carriers . Therefore, second generation TKI, such as afatinib, have been recommended to treat these patients .…”
Section: Discussionmentioning
confidence: 99%
“…The G719X, S768I and L861Q carriers contributed most primary resistance patients in our study. Robust evidence has shown the poor response to the first‐generation TKI in G719X/S768I/L861Q carriers . Therefore, second generation TKI, such as afatinib, have been recommended to treat these patients .…”
Section: Discussionmentioning
confidence: 99%
“…The difference of treatment effect and prognosis may be due to the existence of genetic heterogeneity, such as the different mutation status of EGFR and KRAS genes. Researches showed that after applying Gefitinib and Erlotinib on behalf of TKI therapy, the remission rate of NSCLC patients with EGFR exon 19 deletion and exon 21 L858R point mutation was significantly higher than that of EGFR wild-type patients [20]. However, similar to chemotherapy, TKI therapy also inevitably faced the issue of drug resistance.…”
Section: Discussionmentioning
confidence: 99%
“…nity k ATP, vazebná afinita k TKI je tedy v těchto případech podobná nemutovanému EGFR a výsledkem je primární rezistence k současně používaným TKI [37]. Je k dispozici řada retrospektivních studií hodnotících menší soubory pacientů léčených TKI 1. a 2. generace [52][53][54]. Jediná prospektivní data vyplývají z post hoc analýzy studií Lux-Lung 2, Lux-Lung 3 a Lux-Lung 6, která ukázala, že u 23 pacientů s ins20 genu EGFR byla ORR na afatinib pouze 8,7 %, medián času do progrese (mPFS) 2,7 měsíce a medián celkového přežití (mOS) 9,2 měsíce.…”
Section: S9unclassified
“…V retrospektivních studiích s TKI 1. generace byla zaznamenána částečná odpověď s ORR 20-33 % v případě samostatného výskytu S768I, výrazně lepší výsledky byly u komplexních mutací. Chen et al uvádějí mPFS 2,7 měsíce [60,61]. V post hoc analýze Lux-Lung 2, Lux--Lung 3 a Lux-Lung 6 byla zaznamenána 100% odpověď na léčbu afatinibem, PFS 14,7 měsíce, avšak u 7 z 8 pacientů byla zachycena komplexní mutace s L858R a G719X [55].…”
Section: Bodové Mutace Exonu 20unclassified